Six Sigma As A Means To Enhance Quality Of The Company - Andian Ari Istiningrum; Annisa Ratna Sari (Jurnal Ekonomi dan Pendidikan, 2005)
Six Sigma is a means that can be used to enhance quality by decreasing product defects. Many organizations have succeeded in applying Six Sigma, such as Motorola, General Electric and Allied Signal. To achieve Six Sigma, a process must reduce no more than 3.4 defects per million opportunities.This article tries to describe the definition and process of Six Sigma. Six Sigma can be used in every part of production process. It is important for the organizations to give more attention to quality. The best quality can be achieved if all of the resources and processes are well managed. Six Sigma helps the organizations to measure whether resources and processes are well managed so that better quality can be achieved.Six Sigma has some advantages, such as focus on process, recovery and measurement management, keep the focus accurate, clear and specific, has clear purposes and help the organization to adapt the situation that always changes, uses means and approaches in the proper situation, helps company to create smoother, more effective and more efficient company, recognizes that a little recovery or a big changing is important in the business world, and has no worry to give a big investment to meet the standard.